Review of agricultural market information systems in sub-Saharan Africa - Chiatoh, Maryben; Gyau, Amos (World Agroforestry Centre, 2016)
Agricultural market information systems (MIS) have been promoted to facilitate efficiency in the marketing of agricultural products and provide information for food security monitoring and policy formulations. This study sought to explore the functioning of MIS and to document lessons learned. Fourteen MIS representing different models were selected and reviewed using the Structure-Conduct-Performance model. Findings indicate that the main goal of these systems is to reduce information asymmetries among actors. Information provided is mostly limited to price and dissemination is through the use of different forms of media